Hypokalemia Related to Distal Renal Tubular Acidosis as an Initial Presentation of Primary Sjogren’s Syndrome - I Gede Yasa Asmara; Maruhum Bonar Hasiholan Marbun (Acta Medica Indonesiana, 2024)
Hypokalemia due to loss of potassium through the kidneys can be caused by distal Renal Tubular Acidosis (dRTA). The etiology of dRTA can be primary due to genetic defects or secondary to autoimmune diseases, especially Sjogren’s syndrome (SS). The occurrence of dRTA in SS patients is low, at only 5% of cases. This case was interesting because dRTA was the initial clinical manifestation that led to the diagnosis of SS in the patient. A 48-year-old woman came with complaints of recurrent weakness. The patient was routinely hospitalized with severe hypokalemia and received potassium supplementation. The diagnosis of dRTA was based on repeated weakness, normal blood pressure, severe and recurrent hypokalemia, high urinary potassium, alkaline urine, low plasma bicarbonate, and standard anion gap metabolic acidosis. The diagnosis of SS in this patient was confirmed based on dry eyes, dry mouth, positive Schirmer’s test, and positive autoantibodies to SS-A and Ro-52. There was a delay in the diagnosis of SS for two years in this patient because the complaints were initially subtle and non-specific. The hypokalemia in this patient was secondary to dRTA associated with primary SS. The possibility of an underlying autoimmune disorder should be considered in a patient presenting with recurrent severe hypokalemia. dRTA, as the etiology of hypokalemia, can be a gateway to the diagnosis of SS. In this patient, complaints related to dRTA appeared before the onset of sicca symptoms, and the diagnosis of SS was established.